1999
DOI: 10.1126/science.283.5409.1892
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Transformations in Individual Ultrasmall Biomimetic Containers

Abstract: Individual phospholipid vesicles, 1 to 5 micrometers in diameter, containing a single reagent or a complete reaction system, were immobilized with an infrared laser optical trap or by adhesion to modified borosilicate glass surfaces. Chemical transformations were initiated either by electroporation or by electrofusion, in each case through application of a short (10-microsecond), intense (20 to 50 kilovolts per centimeter) electric pulse delivered across ultramicroelectrodes. Product formation was monitored by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
233
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(240 citation statements)
references
References 24 publications
(15 reference statements)
0
233
0
5
Order By: Relevance
“…Therefore, we can write an enthalpy conservation equation around the droplet boundary: (2) where the first term on the right side refers to the conductive heat flux at the interface of the droplet and the surrounding organic phase; the second term refers to the laser energy absorbed by the droplet; the third term refers to the mass flux leaving the droplet, carrying with it the enthalpy of mixing, which accounts for the energy of phase change to disperse water from pure phase into the organic phase. Were the droplet surrounded by ambient air, as in typical aerosol experiments, the energy of phase change would refer to the latent heat of vaporization.…”
Section: Laser-onmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we can write an enthalpy conservation equation around the droplet boundary: (2) where the first term on the right side refers to the conductive heat flux at the interface of the droplet and the surrounding organic phase; the second term refers to the laser energy absorbed by the droplet; the third term refers to the mass flux leaving the droplet, carrying with it the enthalpy of mixing, which accounts for the energy of phase change to disperse water from pure phase into the organic phase. Were the droplet surrounded by ambient air, as in typical aerosol experiments, the energy of phase change would refer to the latent heat of vaporization.…”
Section: Laser-onmentioning
confidence: 99%
“…However, strategies to obtain approximate solutions have been developed, and has been discussed succinctly in the literature. 13 Typical approaches involve solving Equations (7) and (8) independently first, assuming that the radius is stationary and the transient response of diffusion is instantaneous such that the steady-state solutions to Equations (7) and (8) can be used to evaluate the mass and temperature flux for Equations (1) and (2). This approach is sometimes referred to as "quasi-stationary".…”
Section: Laser-onmentioning
confidence: 99%
See 1 more Smart Citation
“…Since geometric effects play a significant role in the pattern formation, one should be able to take advantage of the powerful microfabrication technology both to explore the consequences of this observation and to provide stringent tests of theoretical models. This system may also find application as a component in a microfluidic screening chip, since it has been shown that subnanoliter vesicles have significant potential as tools for screening of biological and synthetic compounds [14][15][16].…”
mentioning
confidence: 99%
“…In recent years, an increasing variety of materials have been encapsulated within lipid bilayer vesicles. For example, enzymatic reactions including replication and protein synthesis have been demonstrated within the aqueous interior of lipid vesicles (9)(10)(11)(12)(13)(14)(15). Cytoplasmic extracts captured within vesicles maintained enzymatic activity over several days when pore-forming proteins were incorporated in the bilayer (16).…”
mentioning
confidence: 99%